POSSIBILITIES OF FORESTS, FRUITS, MEDICINAL AND AROMATIC HERBS PLACEMENT - Katic, Branko; Savic, Mirjana; Mijajlovic, Nada (Economics of Agriculture, 2006)
Human is returning to nature more and more. Although he with his unreasonable and greed activities carried enormous and probable incorrigible damage, he is only just her little part. Therefore are undertaken and where is possible, synchronous activities an all levels of organization-from local to global extent. Aim of these activities is to decrease level of nature degradation and to coordinate human activities in order to achieve sustainable development witch implicate safe future for next generation. Developed world, is more and more oriented on consumption of products that are produced in harmony with biological and ecological legality or organic agricultural products that are health safe for consumers. Serbia is considered territory who’s environment us endangerment in smaller extent or in other words is more preserved. This is result of numerous circumstances from environmental to historical up to development, and in much smaller level of inhabitants’ sense in last years. Serbia is, thanks to this, suitable for development of organic agriculture, witch should be used in the future as certain comparative. The effects of this orientation could be manifolds. The wild flora and fauna on the principles of sustainable development use of are fit to those tendencies. Products that are results of collection and assembling from nature are including by definition in products of organic production. This paper work is reviewing just these products, their collection, controlled use, processing and placement on domestic and international markets.